Complement selectively elicits glutamate release from nerve endings in different regions of mammal central nervous system. (25th January 2014) - Merega, Elisa; Prisco, Silvia Di; Lanfranco, Massimiliano; Severi, Paolo; Pittaluga, Anna
Abstract Our study was aimed at investigating whether complement, a complex of soluble and membrane‐associated serum proteins, could, in addition to its well‐documented post‐synaptic activity, also pre‐synaptically affect the release of classic neurotransmitters in central nervous system (CNS). Complement (dilution 1 : 10 to 1 : 10000) elicited the release of preloaded [3H]‐d‐aspartate ([3H]d‐ASP) and endogenous glutamate from mouse cortical synaptosomes in a dilution‐dependent manner. It also evoked [3H]d‐ASP release from mouse hippocampal, cerebellar, and spinal cord synaptosomes, as well as from rat and human cortical nerve endings, but left unaltered the release of GABA, [3H]noradrenaline or [3H]acetylcholine. Lowering external Na+ (from 140 to 40 mM) or Ca2+ (from 1.2 to 0.1 mM) ions prevented the 1 : 300 complement‐evoked [3H]d‐ASP release from mouse cortical synaptosomes. Complement‐induced releasing effect was unaltered in synaptosomes entrapped with the Ca2+ ions chelator 1, 2‐bis‐(2‐aminophenoxy) ethane‐N, N, N', N', tetra‐acetic acid or with pertussis toxin. Nifedipine, /ω‐conotoxin GVIA/ω‐conotoxin MVIIC mixture as well as the vesicular ATPase blocker bafilomycin A1 were also inefficacious. The excitatory amino acid transporter blocker DL‐threo‐ß‐benzyloxyaspartic acid, on the contrary, reduced the complement‐evoked releasing effect in a concentration‐dependent manner. We concluded that complement‐induced releasing activity is restricted to glutamatergic nerve endings, where it was accounted for by carrier‐mediated release. Our observations afford new insights into the molecular events accounting for immune and CNS crosstalk. <boxed-text content-type="graphic" id="jnc12650-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> We investigated whether complement, a complex of soluble and membrane‐associated serum proteins, could pre‐synaptically affect the release of classic neurotransmitters in the central nervous system (CNS). Our data provide evidence that complement‐induced releasing activity is restricted to glutamatergic nerve endings, where it was accounted for by carrier‐mediated release. Our observations add new insights to the knowledge of the molecular events accounting for immune and CNS crosstalk. EAAT = excitatory amino acid transporter.